2016
DOI: 10.1186/s12906-016-1304-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of panax notoginseng saponins on the osteogenic differentiation of rabbit bone mesenchymal stem cells through TGF-β1 signaling pathway

Abstract: BackgroundPanax Notoginseng is a well-known Chinese medicinal herb which has been used in China for treatment of bone fracture for hundreds of years. However, the specific biological mechanisms of osteogenic effect of PNS are not well understood.MethodsIn this study, newborn rabbit BMSCs were isolated, and then identified by the positive expression rates of cell surface markers, including CD29, CD45 and HLA-DR, which were detected by flow cytometry(FCM). After the lentivirus-induced cell model of TGF-β1 gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…This observation is proved that bacoside‐A can able to enhance osteogenic differentiation of hBMSCs. This result is concordant with previous studies, which investigated the osteogenic differentiation effects of other saponins compounds on MSCs 35,36,38‐43 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is proved that bacoside‐A can able to enhance osteogenic differentiation of hBMSCs. This result is concordant with previous studies, which investigated the osteogenic differentiation effects of other saponins compounds on MSCs 35,36,38‐43 …”
Section: Discussionsupporting
confidence: 93%
“…It can able to prevent deterioration of bone tissues by enhancing bone formation through osteoblastogenesis and suppressing bone resorption through osteoclastogenesis. Numerous studies have shown about varieties of saponin compounds including tenuigenin, 38 platycodon, 35 panax notoginseng, 36,39 ginsenoside, 40 diosgenin, 41 asperosaponin VI 42 , terpenoid and steroidal saponins, 43 which stimulates osteoblast differentiation and inhibits osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Panax notoginseng has beneficial effects on atherosclerotic diseases such as cardiovascular disease (Yang et al , ), cerebral ischemic disease (Shi et al , ) and other diseases including diabetes (Uzayisenga et al , ; Kitamura et al , ), tumor (Yang et al , ; Li et al , ; Lee et al , ), hepatic injury (Wang et al , ; Zhang et al , ) and bone fracture (Wang et al, ). For in the cardiovascular system, it attenuates atherosclerosis, through inhibiting the formation of foam cells and lowering cholesterol ester level (Jia et al , ), demonstrating antiinflammatory and anti‐adhesion effects (Yuan et al , ) and reducing the size of atherosclerotic plaques (Liu et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies confirmed that Panax notoginseng saponins facilitate the osteogenic process of the skeletal progenitor cells in vitro [ 14 , 15 ], including the proliferation, differentiation, and mineralization. The possible mechanism is that PNS promotes the expression of downstream osteogenesis-related genes by activating ERK and p38 [ 16 ] as well as TGF- β 1 [ 17 ] signaling pathways. Angiogenesis plays an indispensable role in osteogenesis [ 18 ], and the most important pharmacological function of PNS is its vasoactive effect, indicating that PNS could preserve bone mass by promoting the coupling of angiogenesis and osteogenesis during osteoporosis.…”
Section: Introductionmentioning
confidence: 99%